FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT MOTIVASI PETANI SAWIT DALAM PENGEMBALIAN KREDIT DI KOPERASI BAITUL MAAL WATAMWIL DESA SRIKATON KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH - Hendarto, Hendarto; Badrudin, Redy; Yuliarso, M. Zulkarnain (Jurnal AGRISEP, 2012)
The objectives of this research were to find out the level farmer’s motivation in the refunding their loan at Baitul Maal Watamil (BMT) and to determine factors are associated with the level of motivation. This research was held on 15 November 2011 to 15 Desember 2011 in Srikaton Village in Central Bengkulu Regency. The respondents of this research were taken by using census technique. The results of this research indicate that the level of motivations to repay the loans at Baitul Maal Watamil (BMT) could be categorized in medium level or quite good. Then the factors related to the level of farmers motivations in refunding the credit, there were three factors namely. First the level of farming experience. Second the value of collateral and the last level of farmers perceptions of BMT cooperative and the credit program of cooperative it self.